Eksplorasi potensi dan pemetaan rute sport tourism untuk penguatan identitas Desa Wisata Bukit Arang (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2026)
The Bukit Arang tourist area in Lonuo Village, Tilongkabila District, Bone Bolango Regency has great potential as a sport tourism destination, but it has not been optimized due to the lack of documented route mapping, resulting in limited tourist information. This community service activity aims to explore the potential and map sport tourism routes to strengthen the identity of Lonuo Village as a tourist village. The method used is a participatory approach involving students, the village government, the Tourism Awareness Group, and the local community through the stages of field surveys, route mapping, provision of information boards, directional signs, outreach, and evaluation. The results of the activity include the development of a route map depicting the route and strategic points, the installation of map boards at the starting point of the hike, and directional signs made from used tires to assist tourists. This sport tourism route map was tested through the Bukit Arang Trail Fun Run activity. The evaluation showed that the majority of respondents considered this program to be very useful for improving access to information, community participation, and the promotion of the tourism village. The conclusion of this activity is that sport tourism route mapping has proven effective in supporting the development of Bukit Arang Tourism Village.